The northernmost record of the blue-spotted cornetfish from the Mediterranean Sea - OCCHIPINTI-AMBROGI, A.; GALIL, B.S. (Mediterranean Marine Science, 2008)
A school of Fistularia commersonii was sighted off Laigueglia (Italy), Northwestern Ligurian Sea, in August 2008. This fast spreading invasive Indo-Pacific fish was first recorded in the Mediterranean from Israel, and it has since spread clear across the sea. This is the northernmost record from the Mediterranean.